Effectiveness of Mindful Colouring Practices in Reducing Performance Anxiety among Trainee Counselors - Al-Saliti, Rawan Abdul Mahdi Neyef; Hamadneh, Burhan Mahmoud Hamed; Elmorsy, Ghada Nasr; Ismail, Abdelrahim Fathy (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
This study aimed to investigate the effectiveness of Mindful Colouring Practices in reducing performance anxiety among trainee counselors at Yarmouk University in Jordan. The sample consisted of 30 trainee counselors, and a quasi-experimental design was employed to assess the effectiveness of the therapeutic intervention program. The pre-test and post-test evaluations were conducted for both the control group and the experimental group using the Performance Anxiety Scale, which was developed for trainee counselors for the purposes of this study. The results indicated the significant effectiveness of the designed program in reducing performance anxiety levels among the experimental group compared to the control group. This was reflected in the overall anxiety scale as well as in its specific domains: psychological and emotional, cognitive, and physical. Additionally, the results showed no statistically significant differences attributable to gender effects on the total scale or any of the domains, except for the psychological and emotional domain, where differences favored females. Furthermore, no statistically significant differences were found based on academic year in relation to the total scale or in any of the domains, except for the cognitive domain, where third-year students exhibited better results. The study also revealed that no statistically significant differences were attributable to interaction effects between the group and academic year, gender and academic year, or the interaction of group, academic year, and gender. This study highlights the potential of Mindful Colouring Practices as an effective tool for reducing performance anxiety among trainee counselors. The findings suggest that this therapeutic intervention could be a useful addition to counselor training programs.